1989
DOI: 10.1002/1097-0142(19890215)63:4<631::aid-cncr2820630405>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Sequential cytopunctures during preoperative chemotherapy for primary breast carcinoma. Cytomorphologic changes, initial tumor ploidy, and tumor regression

Abstract: Thirty-five patients with large but operable breast carcinoma (T3, NO-N1, MO) received before surgery three cycles of preoperative Adriamycin (doxorubicin), vincristine, cyclophosphamide, methotrexate, 5-fluorouracil (AVCMF) chemotherapy (CT). All patients had sequential cytopunctures for both cytologic examination and flow cytometric DNA analysis (FCM): one before treatment and the three others after each cycle of CT. At cytologic examination, 20 carcinomas showed CT-induced cytomorphologic changes. These cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 11 publications
3
23
0
3
Order By: Relevance
“…To improve our previous results for a better selection of patients, we completed our study on 27 carcinomas, using a cell image processor analysis (SAMBA) with cytologic samples obtained before treatment and after the first cycle, in order to: (1) compare FCM DNA results to those obtained with SAMBA cell image analysis and (2) evaluate chemotherapeutic action on SAMBA morphometric parameters, in particular on textural chromatin parameters.…”
Section: Flow Cytometric (Fcm) Dna and S-mentioning
confidence: 99%
“…To improve our previous results for a better selection of patients, we completed our study on 27 carcinomas, using a cell image processor analysis (SAMBA) with cytologic samples obtained before treatment and after the first cycle, in order to: (1) compare FCM DNA results to those obtained with SAMBA cell image analysis and (2) evaluate chemotherapeutic action on SAMBA morphometric parameters, in particular on textural chromatin parameters.…”
Section: Flow Cytometric (Fcm) Dna and S-mentioning
confidence: 99%
“…First, I would point out that the authors have omitted to reference previous contributions on the same topic (Spyratos et al, 1987;Remvikos et al, 1988a, Briffod et al, 1989. Second, as a cytometrist, I believe that data file histograms should be presented (rather than redrawn ones) as these usually contain extensive information on the quality of the preparations (baseline, noise, skewed peaks, aggregates).…”
Section: Dna Flow Cytometry Of Breast Cancer Fine Needle Aspiratesmentioning
confidence: 99%
“…It was recently shown that DNA-ploidy and Sphase fraction are significantly related to response to cytotoxic chemotherapy (Briffod et al, 1989;Remvikos et al, 1989 Response to the letter from Dr Remvikos…”
Section: Dna Flow Cytometry Of Breast Cancer Fine Needle Aspiratesmentioning
confidence: 99%
See 2 more Smart Citations